2021
DOI: 10.1007/s13202-021-01268-1
|View full text |Cite
|
Sign up to set email alerts
|

Research progress and prospect of Ordovician carbonate rocks in Tahe oilfield: karst feature

Abstract: Inspired by structural geology, karstology, geomorphology, as well as petroleum geology, coupling excellent documented research works and the field investigation, the status and prospect for the studies on karst feature of Tahe oilfield are discussed comprehensively. Results indicate: (a) the majority of research works have appeared since 2000 and can be classified as three categories and 12 subclasses, in which caves, fracture cave systems and fault-karst reservoirs are considered as the main research topics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The reservoir zone is dominated by karst caves and large fractures, in which the caves are large in scale and have various connectivity forms, complex spatial distribution, and strong heterogeneity (for geological information, please refer to Figure 2 in [10]). After long-term, water-driving exploitation, the fractured-vuggy reservoirs have issues with low response and low recovery degrees [11,12]. Consequently, it is urgent to expand the water-driving-related volume of fractured-vuggy reservoirs and improve the oil recovery efficiency of fracturedvuggy reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The reservoir zone is dominated by karst caves and large fractures, in which the caves are large in scale and have various connectivity forms, complex spatial distribution, and strong heterogeneity (for geological information, please refer to Figure 2 in [10]). After long-term, water-driving exploitation, the fractured-vuggy reservoirs have issues with low response and low recovery degrees [11,12]. Consequently, it is urgent to expand the water-driving-related volume of fractured-vuggy reservoirs and improve the oil recovery efficiency of fracturedvuggy reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The Tahe Oilfield, located at the axis of Akekule uplift, Tarim Basin, is a typical fractured-vuggy carbonate reservoir with 9.35 × 108 t of oil and gas reserves [18]. The Tahe Oilfield is mainly composed of Ordovician carbonate fractured-vuggy reservoirs, with oil and gas resources mainly accumulated in caverns and fractures of different sizes [13,19]. The reservoir bodies have different types and in the Yingmai 32-7 plot in the Talimu Oilfield, Xu et al [35,36] divided water breakthrough into slow ascending, benched ascending, and rapid ascending.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, many hundreds of studies about Tahe karst cave reservoirs have been reported, ranging from structural geology, karstification, reservoir characterization, geomodeling, etc. Xu et al (2021) present a review of these progresses.…”
mentioning
confidence: 99%